Impact-resistant plastic packaging material and preparation method thereof

By modified polystyrene, modified cloud -mother, and puppet nitrogen dose -oriented dense refining and thermal pressure to form anti -impact plastic packaging materials, the problem of insufficient anti -impact, antibacterial and flame retardant performance of polystyrene packaging materials , Achieve higher security and reliability.

CN119331419APending Publication Date: 2025-01-21HUIZHOU TIANFU MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411673832.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Polystyrene packaging materials have insufficient impact resistance and do not have sufficient antibacterial and flame retardant properties in humid or warm environments.

Method used

Impact-resistant plastic packaging materials are made by internal mixing of modified polystyrene, modified mica and azobisisobutyronitrile, and hot pressing on a flat vulcanizer. Modified polystyrene reacts with acryloyl chloride, bis(trimethylsilyl)phosphine and methyl p-fluorobenzoate to increase the grafting of phosphorus elements and silicone oil to improve flame retardancy and thermal stability; modified mica reacts with Sodium lignosulfonate reacts with methylguanidine hydrochloride to enhance antibacterial properties.

Benefits of technology

It significantly improves the impact resistance, flame retardant performance and antibacterial performance of the material, so that it has higher security and reliability in a wider application environment.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an impact-resistant plastic packaging material and a preparation method thereof, and relates to the technical field of plastics. When the impact-resistant plastic packaging material is prepared, firstly, single-end hydrogen silicone oil and 3-vinylphenol react to prepare modified silicone oil, polystyrene is grafted with acryloyl chloride, then reacts with bis (trimethylsilyl) phosphine and methyl p-fluorobenzoate, sodium hydroxide is used for hydrolysis, and then reacts with the modified silicone oil to obtain modified polystyrene; secondly, acryloyl chloride and sodium lignin sulfonate are subjected to a reaction to prepare modified sodium lignin sulfonate, pretreated mica and the modified sodium lignin sulfonate are subjected to a reaction, sulfonation acylating chlorination is performed, and then the product and methylguanidine hydrochloride are subjected to a reaction to obtain modified mica; finally, the modified polystyrene, the modified mica and azodiisobutyronitrile are mixed and subjected to hot pressing, and the impact-resistant plastic packaging material is prepared. The impact-resistant plastic packaging material prepared by the invention has impact resistance, flame retardance, antibacterial property and ultraviolet aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastics, in particular to an impact-resistant plastic packaging material and a preparation method thereof. Background Art

[0002] Polystyrene, polyethylene, polypropylene and polyvinyl chloride are collectively known as the four major general-purpose plastics. Plastics play a vital role in the packaging field due to their lightness, durability, easy processing and low cost. They are used to make various packaging materials, such as food packaging, electronic product packaging, daily necessities packaging, etc. These packaging materials not only protect products from damage, but also provide convenient ways to carry and store.

[0003] Polystyrene (PS) is a commonly used plastic in the packaging field. It has good transparency and glossiness, as well as excellent processing performance. However, polystyrene also has some disadvantages. For example, polystyrene has insufficient impact resistance and is easily damaged by external forces, causing the packaging to break or deform. In certain environments, such as humid or warm environments, polystyrene does not have sufficient antibacterial properties, which may lead to bacterial growth and affect the hygiene and safety of the product. In addition, polystyrene has poor flame retardant properties. Once it encounters a fire source, it is easy to cause a fire. In order to solve these problems, it is necessary to modify the polystyrene material to improve its antibacterial, flame retardant and impact resistance, so that its application field is more extensive. Summary of the invention

[0004] The object of the present invention is to provide an impact-resistant plastic packaging material and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: The invention discloses an impact-resistant plastic packaging material, which is obtained by mixing modified polystyrene, modified mica and azobisisobutyronitrile through banburying and hot pressing on a flat vulcanizing machine.

[0006] As an optimization, the modified polystyrene is obtained by reacting polystyrene with acryloyl chloride, then with bis(trimethylsilyl)phosphine, then with methyl p-fluorobenzoate, then hydrolyzed with sodium hydroxide, and then reacted with modified silicone oil; the modified silicone oil is obtained by reacting single-end hydrogen silicone oil with 3-vinylphenol.

[0007] As an optimization, the modified mica is obtained by reacting mica pretreated with allyltrimethoxysilane with methyl methacrylate and modified sodium lignin sulfonate, followed by sulfonation and chlorination, and then reacting with methylguanidine hydrochloride; the modified sodium lignin sulfonate is obtained by reacting lignin with acryloyl chloride.

[0008] A method for preparing an impact-resistant plastic packaging material comprises the following preparation steps: (1) In an anhydrous and oxygen-free, nitrogen-protected environment, single-ended hydrogen silicone oil, Castaplatin catalyst, and toluene are mixed in a mass ratio of 1: (0.001-0.003): (30-40), heated to 40°C and stirred for 2-3h, 0.6-0.8 times the mass of 3-vinylphenol of the single-ended hydrogen silicone oil is added, the reaction is continued at 40°C for 1-2h, the temperature is raised to 85-90°C, the reaction is carried out for 6-8h, and the modified silicone oil is obtained by vacuum rotary evaporation; (2) Mix polystyrene, aluminum chloride, acryloyl chloride and dichloromethane in a mass ratio of 1:(0.7-0.8):(1.1-1.2):(20-30), react for 5-6 hours at room temperature under nitrogen protection, wash with 1 mol / L hydrochloric acid 3 times, then wash with pure water 5 times, add ethanol 3-4 times the volume of dichloromethane, filter and dry at 50-60°C for 6-8 hours to obtain polystyrene containing double bonds; (3) Under nitrogen protection, double bond polystyrene, bis(trimethylsilyl)phosphine, N,N-dimethylformamide, and tetrakis(triphenylphosphine)palladium are mixed in a mass ratio of 1:(0.3-0.5):(20-30):(0.02-0.03), and the mixture is heated to 75-85°C for reaction for 6-7 hours. After the reaction, ethanol 3-4 times the volume of N,N-dimethylformamide is added, and the mixture is filtered and dried at 50-60°C for 6-8 hours to obtain phosphorus-containing polystyrene. Phosphorus-containing polystyrene, methyl parafluorobenzoate, cesium fluoride, and N,N-dimethylformamide are mixed in a mass ratio of 1:(0.5-0.7):(2. 1-2.3): (20-30) mixed, reacted at room temperature for 5-6h, after the reaction was completed, added with N, N-dimethylformamide equal volume of pure water and N, N-dimethylformamide equal volume of dichloromethane mixed for 5min, separated to take the organic phase, dried with anhydrous magnesium sulfate, filtered to remove the anhydrous magnesium sulfate and retain the filtrate, after reduced pressure rotary evaporation, added to 20-30 times the mass of phosphorus-containing polystyrene 10wt% sodium hydroxide solution, heated to 80-90℃ to react for 1-2h, filtered and washed with pure water 3-4 times, dried at 50-60℃ for 7-8h to obtain pre-modified polystyrene; (4) Pre-modified polystyrene, modified silicone oil, zinc chloride and chlorobenzene are mixed in a mass ratio of 1:(1.1-1.2):(0.3-0.5):(20-30), heated to 100-110°C for reaction for 6-7h, ethanol in an amount of 3-4 times the volume of chlorobenzene is added, filtered and dried at 50-60°C for 6-8h to obtain modified polystyrene; (5) Pretreated mica, modified sodium lignin sulfonate, methyl methacrylate, azobisisobutyronitrile, and N,N-dimethylformamide were mixed in a mass ratio of 1: (0.5-0.7): (0.2-0.3): (0.2-0.3): (20-30), heated to 80-90 ° C for reaction for 2-3 hours, filtered and washed with pure water 4 times, and vacuum dried at 50 ° C for 2 hours to obtain lignin-based mica; lignin-based mica and pure water were mixed in a mass ratio of 1: (20-30), 30wt% hydrogen peroxide (0.3-0.5 times the mass of lignin-based mica) was added, heated to 40 ° C for reaction for 40-50 minutes, and then 0.5 times the mass of sodium sulfite and 0.5 times the mass of sodium sulfite were added. 35wt% formaldehyde aqueous solution, using 1mol / L sodium hydroxide to adjust the pH to 8-9, heating to 50°C for reaction for 3-4h, filtering to obtain lignin sulfonate mica; lignin sulfonate mica and dimethyl sulfoxide are mixed in a mass ratio of 1:(20-30), and 6-8 times the mass of thionyl chloride of lignin sulfonate mica is added to react for 3-4h, and filtering to obtain sulfonyl chloride mica; sulfonyl chloride mica, methylguanidine hydrochloride, potassium carbonate, and pure water are mixed in a mass ratio of 1:(0.5-0.7):(1.1-1.2):(20-30), heating to 40-45°C for reaction for 1-2h, filtering and washing with pure water 3-4 times, and vacuum drying at 50°C for 2h to obtain modified mica; (6) The modified polystyrene, modified mica and azobisisobutyronitrile are mixed in an internal mixer for 20-30 minutes at a mixing temperature of 180°C and a rotor speed of 150 r / min. After mixing, the mixture is put into a mold and hot-pressed on a flat vulcanizer for 10 minutes at a temperature of 190°C and a pressure of 10 MPa. The mixture is placed in an oven at 120°C for 2 hours and in an oven at 200°C for 2 hours to obtain an impact-resistant plastic packaging material.

[0009] As an optimization, the model of the single-ended hydrogen silicone oil in step (1) is RH-H222; the model of the Castaplatin catalyst is ACS-Pt-30.

[0010] As an optimization, the polystyrene model in step (2) is GPPS-525.

[0011] As an optimization, the preparation method of the pretreated mica in step (5) is: allyltrimethoxysilane, mica, pure water, and anhydrous ethanol are mixed in a mass ratio of 1:0.5:10:40, the pH value is adjusted to 4 with a 1 mol / L hydrochloric acid solution, the temperature is raised to 60°C for reaction for 3 hours, the mixture is filtered and washed with pure water for 4 times, and vacuum dried at 50°C for 2 hours to obtain the pretreated mica.

[0012] As an optimization, the mica particle size is 100 mesh.

[0013] As an optimization, the preparation method of the modified sodium lignin sulfonate in step (5) is as follows: sodium lignin sulfonate, triethylamine and dioxane are mixed in a mass ratio of 1:1.2:10, mixed at 14°C for 10 minutes, and then an acryloyl chloride solution twice the mass of the sodium lignin sulfonate is added dropwise at a rate of 2 mL / min. After the addition is completed, the reaction is continued for 50 minutes. After the reaction is completed, hydroquinone is added at a mass of 1% of the mass of the sodium lignin sulfonate, and pure water is added at a mass of 20 times the mass of the sodium lignin sulfonate. The mixture is centrifuged at 5°C and 3500 r / min for 10 minutes, and the precipitate after centrifugation is collected and vacuum dried at 50°C for 6 hours to obtain modified sodium lignin sulfonate.

[0014] As an optimization, the acryloyl chloride solution is prepared by mixing acryloyl chloride and dioxane in a mass ratio of 1:10.

[0015] As an optimization, the mass ratio of the modified polystyrene, modified mica and azobisisobutyronitrile in step (6) is 1:(0.3-0.5):(0.05-0.07).

[0016] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing the impact-resistant plastic packaging material, the invention comprises the following steps: firstly, single-end hydrogen silicone oil and 3-vinylphenol are reacted to obtain modified silicone oil; polystyrene is grafted with acryloyl chloride, then reacted with bis(trimethylsilyl)phosphine, then reacted with methyl p-fluorobenzoate, hydrolyzed with sodium hydroxide, and then reacted with the modified silicone oil to obtain modified polystyrene; secondly, acryloyl chloride and sodium lignin sulfonate are reacted to obtain modified sodium lignin sulfonate; mica pretreated with allyltrimethoxysilane is reacted with the modified sodium lignin sulfonate, then sulfonated and chlorinated, and then reacted with methylguanidine hydrochloride to obtain modified mica; and finally, the modified polystyrene, the modified mica and azobisisobutyronitrile are mixed by banburying, and hot pressed by a flat vulcanizer to obtain the impact-resistant plastic packaging material.

[0017] First, a single-end hydrogen silicone oil and 3-vinylphenol are reacted by hydrosilylation to obtain a modified silicone oil containing a phenol group at one end, and polystyrene is grafted with acryloyl chloride by Friedel-Crafts acylation to carry a double bond, and the double bond reacts with the phosphine hydrogen on bis(trimethylsilyl)phosphine and then reacts with methyl p-fluorobenzoate, so that a phosphorus element with a flame retardant function is grafted on the side chain of polystyrene, thereby giving the material good flame retardant properties, and the methyl benzoate group on methyl p-fluorobenzoate is hydrolyzed in the presence of sodium hydroxide to become a carboxylic acid group, and the carboxylic acid group and the phenol group at one end of the modified silicone oil form a benzophenone structure, and the carbonyl group on the benzophenone structure and the adjacent hydroxyl group form an intramolecular chelate ring, which absorbs light energy and converts it into heat energy when exposed to ultraviolet rays, thereby giving the material good resistance to ultraviolet aging; at the same time, the grafting of silicone oil can improve the thermal stability of the material; Secondly, acryloyl chloride and sodium lignin sulfonate are reacted to obtain modified sodium lignin sulfonate. Double bonds are modified on lignin. The surface of mica pretreated with allyltrimethoxysilane also contains double bonds. Modified sodium lignin sulfonate and methyl methacrylate can be polymerized on the surface of pretreated mica under the action of an initiator, thereby strengthening and toughening the packaging material. The lignin on the surface of mica is further sulfonated and chlorinated, and then reacted with methylguanidine hydrochloride to generate a sulfaguanidine structure with antibacterial properties, thereby giving the material good antibacterial properties. Finally, the modified polystyrene, modified mica and azobisisobutyronitrile are mixed and kneaded, and then hot-pressed with a flat vulcanizer to obtain an impact-resistant plastic packaging material. The redundant double bonds in the side chains of the modified polystyrene can undergo self-crosslinking in the presence of an initiator, thereby increasing the crosslinking density and improving the impact resistance of the material. The positively charged methylguanidine hydrochloride on the mica can generate attraction between positive and negative charges with the carboxyl groups on the side chains of the modified polystyrene, thereby making the modified mica uniformly dispersed in the modified polystyrene. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0019] The single-end hydrogen silicone oil used in the following examples and comparative examples is of model RH-H222; the Castaplatin catalyst used is of model ACS-Pt-30; the polystyrene used is of model GPPS-525; the mica particle size used is 100 mesh; the acryloyl chloride solution is prepared by mixing acryloyl chloride and dioxane in a mass ratio of 1:10.

[0020] A method for preparing an impact-resistant plastic packaging material, the method comprising the following preparation steps: (1) In an anhydrous and oxygen-free, nitrogen-protected environment, single-ended hydrogen silicone oil, Castaplatin catalyst, and toluene were mixed in a mass ratio of 1:0.001:30, heated to 40°C and stirred for 3 hours, 0.6 times the mass of 3-vinylphenol of the single-ended hydrogen silicone oil was added, the reaction was continued at 40°C for 2 hours, the temperature was raised to 90°C, the reaction was continued for 8 hours, and the modified silicone oil was obtained by vacuum rotary evaporation; (2) Polystyrene, aluminum chloride, acryloyl chloride and dichloromethane were mixed in a mass ratio of 1:0.7:1.1:20, reacted for 6 hours at room temperature under nitrogen protection, washed 3 times with 1 mol / L hydrochloric acid, then washed 5 times with pure water, added ethanol 3 times the volume of dichloromethane, filtered and dried at 60°C for 8 hours to obtain polystyrene containing double bonds; (3) Under nitrogen protection, double bond polystyrene, bis(trimethylsilyl)phosphine, N,N-dimethylformamide, and tetrakis(triphenylphosphine)palladium were mixed in a mass ratio of 1:0.3:20:0.02, heated to 85°C for 7 hours, and after the reaction, ethanol 3 times the volume of N,N-dimethylformamide was added, and the mixture was filtered and dried at 60°C for 8 hours to obtain phosphorus-containing polystyrene; phosphorus-containing polystyrene, methyl parafluorobenzoate, cesium fluoride, and N,N-dimethylformamide were mixed in a mass ratio of 1:0.5:2.1:20 The mixture was mixed and reacted at room temperature for 6 hours. After the reaction was completed, pure water having an equal volume to N,N-dimethylformamide and dichloromethane having an equal volume to N,N-dimethylformamide were added and mixed for 5 minutes. The organic phase was separated and dried over anhydrous magnesium sulfate. The anhydrous magnesium sulfate was removed by filtration and the filtrate was retained. After vacuum rotary evaporation, the filtrate was added to a 10wt% sodium hydroxide solution having an amount 20 times that of the phosphorus-containing polystyrene. The mixture was heated to 90°C and reacted for 2 hours. The mixture was filtered and washed with pure water for 4 times. The mixture was dried at 60°C for 8 hours to obtain pre-modified polystyrene. (4) Pre-modified polystyrene, modified silicone oil, zinc chloride and chlorobenzene were mixed in a mass ratio of 1:1.1:0.3:20, heated to 110°C for reaction for 7 hours, ethanol with a volume 3 times that of chlorobenzene was added, filtered and dried at 60°C for 8 hours to obtain modified polystyrene; (5) Allyl trimethoxysilane, mica, pure water, and anhydrous ethanol were mixed in a mass ratio of 1:0.5:10:40, and the pH was adjusted to 4 with a 1 mol / L hydrochloric acid solution. The mixture was heated to 60°C for 3 h, filtered, washed with pure water 4 times, and vacuum dried at 50°C for 2 h to obtain pretreated mica. Sodium lignin sulfonate, triethylamine, and dioxane were mixed in a mass ratio of 1:1.2:10, mixed at 14°C for 10 min, and then an acryloyl chloride solution twice the mass of sodium lignin sulfonate was added dropwise. The speed was 2 mL / min. After the addition was completed, the reaction was continued for 50 min. After the reaction was completed, hydroquinone with a mass percentage of 1% of the sodium lignin sulfonate was added, and pure water with a mass percentage of 20 times that of the sodium lignin sulfonate was added. The mixture was centrifuged at 5°C and 3500 r / min for 10 min. The precipitate after centrifugation was collected and vacuum dried at 50°C for 6 h to obtain modified sodium lignin sulfonate. The pretreated mica, modified sodium lignin sulfonate, methyl methacrylate, azobisisobutyronitrile and N,N-dimethylformamide were added in a mass ratio of 1:0.5. :0.2:0.2:20, heated to 90 ° C for reaction for 3 hours, filtered and washed with pure water 4 times, and vacuum dried at 50 ° C for 2 hours to obtain lignin-based mica; lignin-based mica and pure water were mixed at a mass ratio of 1:20, 0.3 times the mass of lignin-based mica was added with 30wt% hydrogen peroxide, heated to 40 ° C for reaction for 50 minutes, and then 0.5 times the mass of lignin-based mica sodium sulfite and 0.5 times the mass of lignin-based mica 35wt% formaldehyde aqueous solution were added, and 1 mol / L sodium hydroxide was used to adjust the pH. H to 9, heating to 50°C for 4h, filtering to obtain lignin sulfonate mica; mixing lignin sulfonate mica and dimethyl sulfoxide at a mass ratio of 1:20, adding thionyl chloride 6 times the mass of lignin sulfonate mica to react for 4h, filtering to obtain sulfonyl chloride mica; mixing sulfonyl chloride mica, methylguanidine hydrochloride, potassium carbonate and pure water at a mass ratio of 1:0.5:1.1:20, heating to 45°C for 2h, filtering and washing with pure water 3 times, and vacuum drying at 50°C for 2h to obtain modified mica; (6) Weigh modified polystyrene, modified mica and azobisisobutyronitrile in a mass ratio of 1:0.3:0.05; mix the modified polystyrene, modified mica and azobisisobutyronitrile in an internal mixer for 30 min at a mixing temperature of 180°C and a rotor speed of 150 r / min; put the mixed materials into a mold, and hot press them on a flat vulcanizer for 10 min at a temperature of 190°C and a pressure of 10 MPa; place them in an oven at 120°C for 2 h and in an oven at 200°C for 2 h to obtain an impact-resistant plastic packaging material.

[0021] A method for preparing an impact-resistant plastic packaging material, the method comprising the following preparation steps: (1) In an anhydrous and oxygen-free, nitrogen-protected environment, single-end hydrogen silicone oil, Castaplatin catalyst, and toluene were mixed in a mass ratio of 1:0.002:35, heated to 40°C and stirred for 2.5 hours, 3-vinylphenol (0.7 times the mass of the single-end hydrogen silicone oil) was added, and the reaction was continued at 40°C for 1.5 hours, and the temperature was raised to 87°C, and the reaction was continued for 7 hours, and the modified silicone oil was obtained by vacuum rotary evaporation; (2) Polystyrene, aluminum chloride, acryloyl chloride and dichloromethane were mixed in a mass ratio of 1:0.75:1.15:25, reacted for 5.5 hours at room temperature under nitrogen protection, washed with 1 mol / L hydrochloric acid for 3 times, then washed with pure water for 5 times, added with ethanol 3.5 times the volume of dichloromethane, filtered and dried at 55°C for 7 hours to obtain polystyrene containing double bonds; (3) Under nitrogen protection, double bond polystyrene, bis(trimethylsilyl)phosphine, N,N-dimethylformamide, and tetrakis(triphenylphosphine)palladium were mixed in a mass ratio of 1:0.4:25:0.025, heated to 80°C for reaction for 6.5 hours, and after the reaction, ethanol 3.5 times the volume of N,N-dimethylformamide was added, filtered, and dried at 55°C for 7 hours to obtain phosphorus-containing polystyrene; phosphorus-containing polystyrene, methyl parafluorobenzoate, cesium fluoride, and N,N-dimethylformamide were mixed in a mass ratio of 1:0.6:2.2:25. The mixture was mixed and reacted at room temperature for 5.5 hours. After the reaction was completed, pure water having an equal volume to N,N-dimethylformamide and dichloromethane having an equal volume to N,N-dimethylformamide were added and mixed for 5 minutes. The organic phase was separated and dried over anhydrous magnesium sulfate. The anhydrous magnesium sulfate was removed by filtration and the filtrate was retained. After vacuum rotary evaporation, the filtrate was added to a 10wt% sodium hydroxide solution having an amount 25 times that of the phosphorus-containing polystyrene. The mixture was heated to 85°C and reacted for 1.5 hours. The mixture was filtered and washed with pure water for 3 times. The mixture was dried at 55°C for 7.5 hours to obtain pre-modified polystyrene. (4) Pre-modified polystyrene, modified silicone oil, zinc chloride and chlorobenzene were mixed in a mass ratio of 1:1.15:0.4:25, heated to 0.5°C and reacted for 6.5 hours, ethanol with a volume of 3.5 times that of chlorobenzene was added, filtered and dried at 55°C for 7 hours to obtain modified polystyrene; (5) Allyl trimethoxysilane, mica, pure water, and anhydrous ethanol were mixed in a mass ratio of 1:0.5:10:40, and the pH was adjusted to 4 with a 1 mol / L hydrochloric acid solution. The mixture was heated to 60°C for 3 h, filtered, washed with pure water 4 times, and vacuum dried at 50°C for 2 h to obtain pretreated mica. Sodium lignin sulfonate, triethylamine, and dioxane were mixed in a mass ratio of 1:1.2:10, mixed at 14°C for 10 min, and then an acryloyl chloride solution twice the mass of sodium lignin sulfonate was added dropwise at a rate of 2:1. mL / min, after the addition was completed, the reaction was continued for 50 min. After the reaction was completed, hydroquinone with a mass percentage of 1% of the sodium lignin sulfonate was added, and pure water with a mass percentage of 20 times that of the sodium lignin sulfonate was added. The mixture was centrifuged at 5°C and 3500 r / min for 10 min. The precipitate after centrifugation was collected and vacuum dried at 50°C for 6 h to obtain modified sodium lignin sulfonate. Pretreated mica, modified sodium lignin sulfonate, methyl methacrylate, azobisisobutyronitrile, and N,N-dimethylformamide were added in a mass ratio of 1:0.6:0.25:0 .25:25, heated to 85°C for reaction for 2.5h, filtered and washed with pure water 4 times, and vacuum dried at 50°C for 2h to obtain lignin-based mica; lignin-based mica and pure water were mixed at a mass ratio of 1:25, 30wt% hydrogen peroxide solution of 0.4 times the mass of lignin-based mica was added, heated to 40°C for reaction for 45min, and then 0.5 times the mass of lignin-based mica sodium sulfite and 0.5 times the mass of lignin-based mica 35wt% formaldehyde aqueous solution were added, and the pH was adjusted to 8.5 with 1mol / L sodium hydroxide. The mixture was heated to 50°C and reacted for 3.5 hours, and lignin sulfonate mica was obtained after filtration; lignin sulfonate mica and dimethyl sulfoxide were mixed in a mass ratio of 1:25, and 7 times the mass of thionyl chloride of lignin sulfonate mica was added to react for 3.5 hours, and sulfonyl chloride mica was obtained after filtration; sulfonyl chloride mica, methylguanidine hydrochloride, potassium carbonate and pure water were mixed in a mass ratio of 1:0.6:0.15:25, heated to 43°C and reacted for 1.5 hours, filtered and washed with pure water for 3 times, and vacuum dried at 50°C for 2 hours to obtain modified mica; (6) Weigh modified polystyrene, modified mica and azobisisobutyronitrile in a mass ratio of 1:0.4:0.06; mix the modified polystyrene, modified mica and azobisisobutyronitrile in an internal mixer for 25 min at a mixing temperature of 180°C and a rotor speed of 150 r / min; put the mixed materials into a mold, and hot press them on a flat vulcanizer for 10 min at a temperature of 190°C and a pressure of 10 MPa; place them in an oven at 120°C for 2 h and in an oven at 200°C for 2 h to obtain an impact-resistant plastic packaging material.

[0022] A method for preparing an impact-resistant plastic packaging material, the method comprising the following preparation steps: (1) In an anhydrous and oxygen-free, nitrogen-protected environment, single-end hydrogen silicone oil, Castaplatin catalyst, and toluene were mixed in a mass ratio of 1:0.003:40, heated to 40°C and stirred for 2 hours, 3-vinylphenol (0.8 times the mass of the single-end hydrogen silicone oil) was added, and the reaction was continued at 40°C for 1 hour, and the temperature was raised to 85°C, and the reaction was continued for 6 hours, and the modified silicone oil was obtained by vacuum rotary evaporation; (2) Polystyrene, aluminum chloride, acryloyl chloride and dichloromethane were mixed in a mass ratio of 1:0.8:1.2:30, reacted for 5 h at room temperature under nitrogen protection, washed 3 times with 1 mol / L hydrochloric acid, then washed 5 times with pure water, added ethanol 4 times the volume of dichloromethane, filtered and dried at 50 °C for 6 h to obtain polystyrene containing double bonds; (3) Under nitrogen protection, double bond polystyrene, bis(trimethylsilyl)phosphine, N,N-dimethylformamide, and tetrakis(triphenylphosphine)palladium were mixed in a mass ratio of 1:0.5:30:0.03, heated to 75°C for 6 hours, and after the reaction, ethanol 4 times the volume of N,N-dimethylformamide was added, and the mixture was filtered and dried at 50°C for 6 hours to obtain phosphorus-containing polystyrene; phosphorus-containing polystyrene, methyl parafluorobenzoate, cesium fluoride, and N,N-dimethylformamide were mixed in a mass ratio of 1:0.7:2.3:30:0. The mixture was mixed and reacted at room temperature for 5 hours. After the reaction was completed, pure water having an equal volume to N,N-dimethylformamide and dichloromethane having an equal volume to N,N-dimethylformamide were added and mixed for 5 minutes. The organic phase was separated and dried over anhydrous magnesium sulfate. The anhydrous magnesium sulfate was removed by filtration and the filtrate was retained. After vacuum rotary evaporation, the filtrate was added to a 10wt% sodium hydroxide solution having a mass that was 30 times that of the phosphorus-containing polystyrene. The mixture was heated to 80°C and reacted for 1 hour. The mixture was filtered and washed with pure water for 4 times. The mixture was dried at 50°C for 7 hours to obtain pre-modified polystyrene. (4) Pre-modified polystyrene, modified silicone oil, zinc chloride and chlorobenzene were mixed in a mass ratio of 1:1.2:0.5:30, heated to 100°C for reaction for 6 hours, ethanol in an amount 4 times the volume of chlorobenzene was added, filtered and dried at 50°C for 6 hours to obtain modified polystyrene; (5) Allyl trimethoxysilane, mica, pure water, and anhydrous ethanol were mixed in a mass ratio of 1:0.5:10:40, and the pH was adjusted to 4 with a 1 mol / L hydrochloric acid solution. The mixture was heated to 60°C for 3 h, filtered, washed with pure water 4 times, and vacuum dried at 50°C for 2 h to obtain pretreated mica. Sodium lignin sulfonate, triethylamine, and dioxane were mixed in a mass ratio of 1:1.2:10, mixed at 14°C for 10 min, and then an acryloyl chloride solution twice the mass of sodium lignin sulfonate was added dropwise. The speed was 2 mL / min. After the addition was completed, the reaction was continued for 50 min. After the reaction was completed, hydroquinone with a mass percentage of 1% of the sodium lignin sulfonate was added, and pure water with a mass percentage of 20 times that of the sodium lignin sulfonate was added. The mixture was centrifuged at 5°C and 3500 r / min for 10 min. The precipitate after centrifugation was collected and vacuum dried at 50°C for 6 h to obtain modified sodium lignin sulfonate. The pretreated mica, modified sodium lignin sulfonate, methyl methacrylate, azobisisobutyronitrile and N,N-dimethylformamide were added in a mass ratio of 1:0.7. :0.3:0.3:30, heated to 80°C for reaction for 2h, filtered and washed with pure water 4 times, and vacuum dried at 50°C for 2h to obtain lignin-based mica; lignin-based mica and pure water were mixed at a mass ratio of 1:30, 0.5 times the mass of lignin-based mica was added with 30wt% hydrogen peroxide, heated to 40°C for reaction for 40min, and then 0.5 times the mass of lignin-based mica sodium sulfite and 0.5 times the mass of lignin-based mica were added with 35wt% formaldehyde aqueous solution, and 1mol / L sodium hydroxide was used to adjust the pH. H to 8, heating to 50°C for reaction for 3h, filtering to obtain lignin sulfonate mica; mixing lignin sulfonate mica and dimethyl sulfoxide at a mass ratio of 1:30, adding thionyl chloride with a mass of 8 times that of the lignin sulfonate mica to react for 3h, filtering to obtain sulfonyl chloride mica; mixing sulfonyl chloride mica, methylguanidine hydrochloride, potassium carbonate and pure water at a mass ratio of 1:0.7:1.2:30, heating to 40°C for reaction for 1h, filtering and washing with pure water 3 times, and vacuum drying at 50°C for 2h to obtain modified mica; (6) Weigh modified polystyrene, modified mica and azobisisobutyronitrile in a mass ratio of 1:0.5:0.07; mix the modified polystyrene, modified mica and azobisisobutyronitrile in an internal mixer for 20 min at a mixing temperature of 180°C and a rotor speed of 150 r / min; put the mixed materials into a mold; and hot press them on a flat vulcanizer for 10 min at a hot pressing temperature of 190°C and a pressure of 10 MPa; place them in an oven at 120°C for 2 h and in an oven at 200°C for 2 h to obtain an impact-resistant plastic packaging material.

[0023] Comparative Example 1: The preparation method of the impact-resistant plastic packaging material of Comparative Example 1 differs from that of Example 2 in that step (4) is not included, and step (6) is modified as follows: pre-modified polystyrene, modified mica and azobisisobutyronitrile are weighed in a mass ratio of 1:0.4:0.06; the modified polystyrene, modified mica and azobisisobutyronitrile are mixed in an internal mixer for 25 min at a mixing temperature of 180° C. and a rotor speed of 150 r / min; after mixing, the mixture is put into a mold, hot-pressed on a flat vulcanizer for 10 min at a hot-pressing temperature of 190° C. and a pressure of 10 MPa; the mixture is placed in an oven at 120° C. for 2 h and in an oven at 200° C. for 2 h to obtain an impact-resistant plastic packaging material.

[0024] Comparative Example 2: The preparation method of the impact-resistant plastic packaging material of Comparative Example 2 differs from that of Example 2 in that steps (3) to (4) are not included, and step (2) is modified as follows: polystyrene, aluminum chloride, acryloyl chloride and dichloromethane are mixed in a mass ratio of 1:0.75:1.15:25, reacted for 5.5 hours at room temperature under nitrogen protection, washed three times with 1 mol / L hydrochloric acid, then washed five times with pure water, added with ethanol in an amount 3.5 times the volume of dichloromethane, filtered, and dried at 55°C for 7 hours to obtain modified polystyrene.

[0025] Comparative Example 3: The difference between the preparation method of the impact-resistant plastic packaging material of Comparative Example 3 and Example 2 is that step (5) is modified as follows: allyltrimethoxysilane, mica, pure water, and anhydrous ethanol are mixed in a mass ratio of 1:0.5:10:40, the pH value is adjusted to 4 with a 1 mol / L hydrochloric acid solution, the temperature is raised to 60°C for reaction for 3 hours, the mixture is filtered and washed with pure water for 4 times, and vacuum dried at 50°C for 2 hours to obtain modified mica.

[0026] Test Example 1: Flame retardant performance test: Test method: According to the standard GB / T2406-1993, the impact-resistant plastic packaging materials prepared in the examples and comparative examples were tested for limiting oxygen index using a JF-3 instrument. The results are shown in Table 1.

[0027] Table 1 Limiting oxygen index (%) Limiting oxygen index (%) Example 1 32.8 Comparative Example 1 28.6 Example 2 32.8 Comparative Example 2 23.4 Example 3 33.1 Comparative Example 3 31.6 From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the impact-resistant plastic packaging material prepared by the present invention has good flame retardant properties.

[0028] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 2, indicating that a modified silicone oil containing a phenol group at one end is prepared by a silylation reaction between a single-end hydrogen silicone oil and 3-vinylphenol, and polystyrene is grafted with acryloyl chloride by a Friedel-Crafts acylation reaction, thereby carrying a double bond, and the double bond reacts with the phosphine hydrogen on bis(trimethylsilyl)phosphine and then reacts with methyl p-fluorobenzoate, so that phosphorus elements with flame retardant function are grafted on the side chains of polystyrene, thereby giving the material good flame retardant properties.

[0029] Test Example 2: Antibacterial performance test: Test method: Referring to the standard QB / T 2591-2003, the antibacterial properties of the impact-resistant plastic packaging materials prepared in the examples and comparative examples were tested by the film pasting method, and the strain used in the test was Escherichia coli. The results are shown in Table 2.

[0030] Table 2 Antibacterial rate (%) Antibacterial rate (%) Example 1 97.43 Comparative Example 1 97.35 Example 2 97.47 Comparative Example 2 97.38 Example 3 97.50 Comparative Example 3 24.51 From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 2, it can be found that the impact-resistant plastic packaging material prepared by the present invention has good antibacterial properties.

[0031] By comparison, the antibacterial rates of Examples 1 to 3 are greater than that of Comparative Example 3, indicating that modified sodium lignin sulfonate is prepared by reacting acryloyl chloride and sodium lignin sulfonate, lignin is modified with double bonds, and the mica surface pretreated with allyltrimethoxysilane also contains double bonds. Modified sodium lignin sulfonate and methyl methacrylate can be polymerized on the pretreated mica surface under the action of an initiator, and the lignin on the mica surface is further sulfonated and chlorinated, and then reacted with methylguanidine hydrochloride to generate a sulfaguanidine structure with antibacterial properties, thereby giving the material good antibacterial properties.

[0032] Test Example 3: Impact resistance test: Test method: The impact-resistant plastic packaging materials prepared in the examples and comparative examples were cut into samples with a size of 20 mm*10 mm, and the samples were tested for impact strength using an XJUD-22 digital cantilever beam impact tester, with an impact velocity of 3.8 m / s and a pendulum pre-elevation angle of 150° under dynamic load. The results are shown in Table 3.

[0033] Test of anti-ultraviolet aging performance: Test method: Cut the impact-resistant plastic packaging materials prepared in the examples and comparative examples into samples with a size of 20 mm*10 mm, and place the samples in a UV light box. There are 4 Q-LabUVA340 UV lamps in the light box, with a distance of 10 cm between the lamps, a distance of 5 cm between the sample and the lamp, and a central wavelength of 340 nm and an intensity of 13 mW / cm2 The size of the light box is 130cm*45cm*20cm, and the irradiation time is 720h. After the irradiation, the impact strength before and after UV aging is tested according to the impact resistance test method, and the impact strength retention rate is calculated. The results are shown in Table 3.

[0034] Table 3 Impact strength (KJ / m2) Impact strength retention rate (%) Example 1 62.13 97.36 Example 2 62.21 97.41 Example 3 62.27 97.42 Comparative Example 1 60.76 96.75 Comparative Example 2 60.51 47.56 Comparative Example 3 21.32 76.43 From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 3, it can be found that the impact-resistant plastic packaging material prepared by the present invention has good impact resistance and anti-ultraviolet aging performance.

[0035] The impact strength of Examples 1 to 3 is greater than that of Comparative Examples 1 to 3, and the impact strength retention rate of Examples 1 to 3 is greater than that of Comparative Example 2, indicating that the modified polystyrene, modified mica, and azobisisobutyronitrile are mixed by internal kneading and hot-pressed with a flat vulcanizer to obtain an impact-resistant plastic packaging material, and the redundant double bonds in the side chains of the modified polystyrene can undergo self-crosslinking in the presence of an initiator, thereby increasing the crosslinking density and improving the impact resistance of the material.

[0036] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. An impact-resistant plastic packaging material, characterized in that: The impact-resistant plastic packaging material is obtained by mixing modified polystyrene, modified mica and azobisisobutyronitrile through banburying and hot pressing on a flat vulcanizing machine; The modified polystyrene is obtained by reacting polystyrene with acryloyl chloride, then with bis(trimethylsilyl)phosphine, then with methyl p-fluorobenzoate, then hydrolyzed with sodium hydroxide, and then reacted with modified silicone oil; the modified silicone oil is obtained by reacting single-end hydrogen silicone oil with 3-vinylphenol; The modified mica is obtained by reacting mica pretreated with allyltrimethoxysilane with methyl methacrylate and modified sodium lignin sulfonate, followed by sulfonation and chlorination, and then reacting with methylguanidine hydrochloride; the modified sodium lignin sulfonate is obtained by reacting lignin with acryloyl chloride.

2. A method for preparing an impact-resistant plastic packaging material, characterized in that: The method comprises the following preparation steps: (1) In an anhydrous and oxygen-free, nitrogen-protected environment, single-ended hydrogen silicone oil, Castaplatin catalyst, and toluene are mixed in a mass ratio of 1: (0.001-0.003): (30-40), heated to 40°C and stirred for 2-3h, 0.6-0.8 times the mass of 3-vinylphenol of the single-ended hydrogen silicone oil is added, the reaction is continued at 40°C for 1-2h, the temperature is raised to 85-90°C, the reaction is carried out for 6-8h, and the modified silicone oil is obtained by vacuum rotary evaporation; (2) Mix polystyrene, aluminum chloride, acryloyl chloride and dichloromethane in a mass ratio of 1:(0.7-0.8):(1.1-1.2):(20-30), react for 5-6 hours at room temperature under nitrogen protection, wash with 1 mol / L hydrochloric acid 3 times, then wash with pure water 5 times, add ethanol 3-4 times the volume of dichloromethane, filter and dry at 50-60°C for 6-8 hours to obtain polystyrene containing double bonds; (3) Under nitrogen protection, double bond polystyrene, bis(trimethylsilyl)phosphine, N,N-dimethylformamide, and tetrakis(triphenylphosphine)palladium are mixed in a mass ratio of 1:(0.3-0.5):(20-30):(0.02-0.03), and the mixture is heated to 75-85°C for reaction for 6-7 hours. After the reaction, ethanol 3-4 times the volume of N,N-dimethylformamide is added, and the mixture is filtered and dried at 50-60°C for 6-8 hours to obtain phosphorus-containing polystyrene. Phosphorus-containing polystyrene, methyl parafluorobenzoate, cesium fluoride, and N,N-dimethylformamide are mixed in a mass ratio of 1:(0.5-0.7):(2. 1-2.3): (20-30) mixed, reacted at room temperature for 5-6h, after the reaction was completed, added with N, N-dimethylformamide equal volume of pure water and N, N-dimethylformamide equal volume of dichloromethane mixed for 5min, separated to take the organic phase, dried with anhydrous magnesium sulfate, filtered to remove the anhydrous magnesium sulfate and retain the filtrate, after reduced pressure rotary evaporation, added to 20-30 times the mass of phosphorus-containing polystyrene 10wt% sodium hydroxide solution, heated to 80-90℃ to react for 1-2h, filtered and washed with pure water 3-4 times, dried at 50-60℃ for 7-8h to obtain pre-modified polystyrene; (4) Pre-modified polystyrene, modified silicone oil, zinc chloride and chlorobenzene are mixed in a mass ratio of 1:(1.1-1.2):(0.3-0.5):(20-30), heated to 100-110°C for reaction for 6-7h, ethanol in an amount of 3-4 times the volume of chlorobenzene is added, filtered and dried at 50-60°C for 6-8h to obtain modified polystyrene; (5) Pretreated mica, modified sodium lignin sulfonate, methyl methacrylate, azobisisobutyronitrile, and N,N-dimethylformamide were mixed in a mass ratio of 1: (0.5-0.7): (0.2-0.3): (0.2-0.3): (20-30), heated to 80-90 ° C for reaction for 2-3 hours, filtered and washed with pure water 4 times, and vacuum dried at 50 ° C for 2 hours to obtain lignin-based mica; lignin-based mica and pure water were mixed in a mass ratio of 1: (20-30), 30wt% hydrogen peroxide (0.3-0.5 times the mass of lignin-based mica) was added, heated to 40 ° C for reaction for 40-50 minutes, and then 0.5 times the mass of sodium sulfite and 0.5 times the mass of sodium sulfite were added. 35wt% formaldehyde aqueous solution, using 1mol / L sodium hydroxide to adjust the pH to 8-9, heating to 50°C for reaction for 3-4h, filtering to obtain lignin sulfonate mica; lignin sulfonate mica and dimethyl sulfoxide are mixed in a mass ratio of 1:(20-30), and 6-8 times the mass of thionyl chloride of lignin sulfonate mica is added to react for 3-4h, and filtering to obtain sulfonyl chloride mica; sulfonyl chloride mica, methylguanidine hydrochloride, potassium carbonate, and pure water are mixed in a mass ratio of 1:(0.5-0.7):(1.1-1.2):(20-30), heating to 40-45°C for reaction for 1-2h, filtering and washing with pure water 3-4 times, and vacuum drying at 50°C for 2h to obtain modified mica; (6) The modified polystyrene, modified mica and azobisisobutyronitrile are mixed in an internal mixer for 20-30 minutes at a mixing temperature of 180°C and a rotor speed of 150 r / min. After mixing, the mixture is put into a mold and hot-pressed on a flat vulcanizer for 10 minutes at a temperature of 190°C and a pressure of 10 MPa. The mixture is placed in an oven at 120°C for 2 hours and in an oven at 200°C for 2 hours to obtain an impact-resistant plastic packaging material.

3. The method for preparing an impact-resistant plastic packaging material according to claim 2, characterized in that: The model of the single-ended hydrogen silicone oil in step (1) is RH-H222; the model of the Castaplatin catalyst is ACS-Pt-30.

4. The method for preparing an impact-resistant plastic packaging material according to claim 2, characterized in that: The polystyrene model in step (2) is GPPS-525.

5. The method for preparing an impact-resistant plastic packaging material according to claim 2, characterized in that: The preparation method of the pretreated mica in step (5) is as follows: allyltrimethoxysilane, mica, pure water and anhydrous ethanol are mixed in a mass ratio of 1:0.5:10:40, the pH value is adjusted to 4 with a 1 mol / L hydrochloric acid solution, the temperature is raised to 60°C for reaction for 3 hours, the mixture is filtered and washed with pure water for 4 times, and vacuum dried at 50°C for 2 hours to obtain the pretreated mica.

6. The method for preparing an impact-resistant plastic packaging material according to claim 2, characterized in that: The preparation method of the modified sodium lignin sulfonate in step (5) is as follows: sodium lignin sulfonate, triethylamine and dioxane are mixed in a mass ratio of 1:1.2:10, mixed at 14°C for 10 minutes, and then dripped with an acryloyl chloride solution twice the mass of the sodium lignin sulfonate at a dripping speed of 2 mL / min. After the dripping is completed, the reaction is continued for 50 minutes. After the reaction is completed, hydroquinone is added at 1% of the mass of the sodium lignin sulfonate, and pure water is added at 20 times the mass of the sodium lignin sulfonate. The mixture is centrifuged at 5°C and 3500 r / min for 10 minutes, and the precipitate after centrifugation is collected and vacuum dried at 50°C for 6 hours to obtain the modified sodium lignin sulfonate.

7. The method for preparing an impact-resistant plastic packaging material according to claim 2, characterized in that: The mass ratio of the modified polystyrene, modified mica and azobisisobutyronitrile in step (6) is 1:(0.3-0.5):(0.05-0.07).

8. The method for preparing an impact-resistant plastic packaging material according to claim 5, characterized in that The mica particle size is 100 mesh.

9. The method for preparing an impact-resistant plastic packaging material according to claim 6, characterized in that The acryloyl chloride solution is prepared by mixing acryloyl chloride and dioxane in a mass ratio of 1:10.

Citation Information

Cited By

  • Preparation method of multifunctional medical instrument packaging composite material

    CN120461910B